Design of a novel test cell to study the influence of water activity on the thermal resistance of Salmonella in low-moisture foods. (September 2017) - Tadapaneni, Ravi Kiran; Syamaladevi, Roopesh M.; Villa-Rojas, Rossana; Tang, Juming
Abstract: A novel test cell was developed to study the influence of water activity (aw ) on thermal inactivation of food pathogens in low-moisture foods (LMF). The cell consisted of multiple wells with a shared headspace; aw of the inoculated food sample was controlled by lithium chloride (LiCl) solution of selected molality during heating. The performance of the test cell was evaluated by studying sample heating uniformity using finite element simulation and by comparing measured headspace relative humidities (RH) with predicted RH provided by LiCl solutions. The new cells were used to determine thermal resistance (D-value) of Salmonella at 80 °C in organic wheat flour (OWF) maintained at aw of 0.45. The D-value of Salmonella was also determined in conventional thermal death time test cells in which aw of OWF samples increased from 0.45 at room temperature to 0.73 at 80 °C according to the measured isotherm. The results demonstrated that aw significantly influenced the D-values of Salmonella, and the new test cells can be used to directly relate thermal resistance of food pathogens to water activities of LMF at processing temperatures. Highlights: A novel test cell was developed to control the water activity of organic wheat flour (OWF) at high temperatures. Moisture sorption isotherms of OWF were determined at 20 and 80 °C. Thermal resistance of Salmonella in OWF was determined by the new cells and compared to conventional (TDT) cells. Water activity of OWF influenced thermal resistance of Salmonella .